ASURANSI DALAM PERSPEKTIF ISLAM - Purnamasari, Shofia (Islamic Economics and Business Faculty of UIN Antasari, 2016)
Abstract: Takaful and its development in the Islamic world become urgent as in Indonesia which is the majority of Muslim population. In Islamic teachings also contained the substance of the insurance regulation. Insurance which is appropriate to Islamic law was able to avoid the insurance operational principle of gharar, maysir, and usury. Due to that basis, then thought out and formulated appropriate insurance forms of Islamic law. In principle, Islamic economic studies has always put forward the principles of fairness, help each other, avoid injustice, the prohibition of usury (interest), the principle of proft and loss sharing as well as the removalof gharar element. Gharar element in conventional insurance lies in the uncertainty about the rights of policy holders, and the resources that they use to cover claims. Maysir element lies in the possibility of the benefciary at the expense of others. While usury elements lies in revenue from money.Abstrak: Asuransi syariah dan perkembangannya di dalam dunia islam menjadi hal urgen. Begitupun di Indonesia yang notabene penduduknya mayoritas beragama Islam. Di dalam ajaran Islam juga termuat substansi mengenai peraturan perasuransian. Asuransi yang sesuai hukum islam ternyata mampu menghindarkan prinsip operasional asuransi dari unsur gharar, maysir, dan riba. Atas landasan itulah, kemudian dipikirkan dan dirumuskan bentuk asuransi yang sesuai syariat Islam. Secara prinsipil kajian ekonomi islam selalu mengedepankan asas keadilan, tolong – menolong, menghindari kezaliman, pengharaman riba (bunga), berprinsip proft and loss sharring serta penghilangan unsur gharar. Unsur Gharar dalam asuransi konvensional terletak pada ketidakpastian tentang hak pemegang polis dan sumber dana yang di pakai untuk menutup klaim. Unsur maysir terletak pada kemungkinan adanya pihak yang diuntungkan di atas kerugian orang lain. Sedangkan unsur riba terdapa pada perolehan pendapatan dari membungakan uang.Keywords: deposit, gharar, riba, konvensional.